Model Infographic Content dan Brand Equity dalam Meningkatkan Minat Kunjung Desa Wisata Kabupaten Kerinci Provinsi Jambi - Ade Perdana Siregar (J-MAS (Jurnal Manajemen dan Sains), 2022)
Submission of information digitally will quickly reach the recipient of the information without limits. Promotions are carried out with digital media today with various methods, one of which is by creating infographic content. Infographics are growing rapidly in mass media after being digitally designed that cannot be told, only in the form of text and photos. Infographics are a new method of conveying information that is more effective. Besides marketing with infographics, tourists will be able to confidently convince themselves by seeing the value of a tourism product and the value of the product can be symbolized by brand equity. The objectives of this study are: (1) to examine the effect of brand equity on visiting interest; (2) examine the effect of brand equity on infographic content; (3) examine the effect of infographic content on visiting interest; (4) examines the role of infographic content in being able to mediate the influence of brand equity on visiting interest. The population is tourists visiting tourist villages in Kerinci Regency while the sample is 200 visitors to tourist villages in Kerinci Regency. The method used is the Structural Equation Modeling (SEM) measurement using SmartPLS software. The results showed that brand equity has a positive effect on infographic content, brand equity has a positive effect on visiting interest, infographic content has a positive effect on visiting interest, infographic content can play a positive role as mediating the influence of brand equity on visiting interest.